2021
DOI: 10.1212/wnl.0000000000012698
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter Validation of a Deep Learning Detection Algorithm for Focal Cortical Dysplasia

Abstract: Objective.To test the hypothesis that a multicenter-validated computer deep learning algorithm detects MRI-negative focal cortical dysplasia (FCD).Methods.We used clinically-acquired 3D T1-weighted and 3D FLAIR MRI of 148 patients (median age, 23 years [range, 2-55]; 47% female) with histologically-verified FCD at nine centers to train a deep convolutional neural network (CNN) classifier. Images were initially deemed as MRI-negative in 51% of cases, in whom intracranial EEG determined the focus. For risk strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 43 publications
1
78
1
1
Order By: Relevance
“…However, being limited by small numbers of patients and data acquired from only one or two MRI scanners can lead to large error bars on estimates of sensitivity and specificity (Varoquaux, 2018) and limited generalisability due lack of diversity in training data. Progress is also being made on automated volumetric MRI methods (David et al, 2021;Gill et al, 2021;House et al, 2021), however datasets have tended to be restricted either to histopathologically confirmed FCD type II cohorts, or single sites. Through creating a large dataset including both paediatric and adult patients across multiple sites and MRI scanners as well as including all FCD histopathological subtypes, we aimed to address these limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, being limited by small numbers of patients and data acquired from only one or two MRI scanners can lead to large error bars on estimates of sensitivity and specificity (Varoquaux, 2018) and limited generalisability due lack of diversity in training data. Progress is also being made on automated volumetric MRI methods (David et al, 2021;Gill et al, 2021;House et al, 2021), however datasets have tended to be restricted either to histopathologically confirmed FCD type II cohorts, or single sites. Through creating a large dataset including both paediatric and adult patients across multiple sites and MRI scanners as well as including all FCD histopathological subtypes, we aimed to address these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologically FCDs are characterised by alterations in cortical thickness, blurring at the greywhite matter boundary, folding abnormalities, and T2 or FLAIR signal intensity changes (Colombo et al, 2012). Approaches to improving the detection of FCDs have involved improved scanner protocols (Bernasconi et al, 2019) and field strengths (Bartolini et al, 2019;Wang et al, 2020) as well as automated volumetric (David et al, 2021;Gill et al, 2021Gill et al, , 2018House et al, 2021;Huppertz et al, 2005) and surface-based (Adler et al, 2017;Ahmed et al, 2015;Hong et al, 2014;Jin et al, 2018) post-processing methods.…”
Section: Introductionmentioning
confidence: 99%
“… 22 25 A recent multicenter-validated study showed that DL using multimodal MRI data could reliably identify previous MRI-negative FCD lesions, suggesting that DL shows promise for assisting non-expert clinicians in this challenging diagnosis. 26 …”
Section: Artificial Intelligence Applications For Epilepsy Diagnosis ...mentioning
confidence: 99%
“…[22][23][24][25] A recent multicentervalidated study showed that DL using multimodal MRI data could reliably identify previous MRI-negative FCD lesions, suggesting that DL shows promise for assisting non-expert clinicians in this challenging diagnosis. 26 AI methods can also combine imaging and clinical data to build models for predicting clinical outcomes in patients with epilepsy. 27 For example, automated volumetric MRI measurements incorporated into statistical models help to predict postoperative seizure outcomes in TLE and frontal lobe epilepsy (FLE), revealing that subtle cortical atrophy beyond the surgical resection influences seizure outcome.…”
Section: Artificial Intelligence Applications For Epilepsy Diagnosis ...mentioning
confidence: 99%
“…In the Research Article “Multicenter Validation of a Deep Learning Detection Algorithm for Focal Cortical Dysplasia” by Gill et al, 1 several links to the supplemental content were omitted in the final manuscript. The article has now been replaced by a corrected version with the links included.…”
mentioning
confidence: 99%